The dual role of interleukin-6 in Crohn’s disease pathophysiology - Alhendi, Ala’; Naser, Saleh A. (Frontiers in Immunology, 2023)
Interleukin-6 (IL-6) is a key mediator cytokine of the immune response as well as a regulator of many physiological and pathological processes. In Crohn’s disease (CD), cytokine imbalance rules the intestinal microenvironment and leads to chronic inflammation of the gut. Pro-inflammatory cytokines are generally upregulated in IBD including TNF-α and IL-6. Consequently, drugs that target these cytokines have been long sought and approved. Despite the short-term success in treating CD patients with anti-TNFα, many patients stop responding to treatment which made IL-6 an alternative target to alleviate inflammation in these patients. IL-6 has long been approached as part of the therapeutic strategies to treat CD and other inflammatory disorders. Clinical trials of CD patients have targeted IL-6 signaling in different mechanisms: blocking IL-6, neutralizing IL-6 receptor (IL-6R) or trapping the soluble IL-6/IL-6R complex. These trials have faced challenges and side effects in patients like gastrointestinal perforations and ulcers, all of which highlight the dual role of IL-6 during intestinal inflammation and the need for this cytokine for intestinal tissue integrity. IL-6 is involved in a complex of upstream regulators and downstream signaling cascades and maintaining a physiological level of IL-6 in the blood and in the intestine is key for achieving health and homeostasis. In this review, we describe IL-6 biology and signaling and its involvement in intestinal health and inflammation. We also discuss the current strategies of targeting IL-6 pathways in CD patients, as well as molecular regulators representing potential therapeutic targets for IL-6 attenuation.